Botulinum toxin type A in the treatment of phantom pain: a successful case study - D.V. Dmytriiev; P.A. Borozenets; Yu.V. Oleshko; V.V. Sirosh (Медицина неотложных состояний)
Due to active hostilities, the number of patients experiencing phantom pain has sharply increased nowadays. In case of limb amputation, 50 % of patients experience phantom pain, and about 70 % report phantom sensations. This issue is extremely relevant and insufficiently studied in modern medicine. Only a few medical institutions provide adequate management of chronic pain syndrome (including phantom pain). It is also worth noting that untreated phantom pain makes the use of prosthesis impossible, which, in turn, nullifies the potential for complete socialization and adaptation of the patient, thereby increasing the burden not only on the medical system but also on social services. The use of neuraxial analgesia methods has proven to be an effective treatment for this pathology; however, the short duration of effect encourages further exploration and research. This case report highlights the combination of neuraxial methods with the use of botulinum toxin type A for the treatment of phantom pain in patients with traumatic limb amputations. Given the limited number of relevant studies and the small sample size regarding the use of botulinum toxin type A, we would like to present our own clinical case with a positive outcome.